2015
DOI: 10.1088/1748-6041/10/2/025012
|View full text |Cite
|
Sign up to set email alerts
|

Porous alumina, zirconia and alumina/zirconia for bone repair: fabrication, mechanical and in vitro biological response

Abstract: Zirconia (ZrO2) and alumina (Al2O3) based ceramics are widely used for load-bearing applications in bone repair due to their excellent mechanical properties and biocompatibility. They are often regarded as bioinert since no direct bone-material interface is created unless a porous structure intercedes, leading to better bone bonding. In this regard, investigating interactions between cells and porous ceramics is of great interest. In the present study, we report on the successful fabrication of sintered alumin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 40 publications
3
35
0
2
Order By: Relevance
“…In previous studies, we investigated the osteogenic potential of pre-osteoblasts on porous magnesia and yttria-stabilized zirconia ceramics (Hadjicharalambous et al, 2015b ), as well as the pre-osteoblastic cell response on zirconia, alumina, and zirconia/alumina composite (Hadjicharalambous et al, 2015a ). The objective of this study was to investigate the effect of zirconia and alumina ceramic substrate porosity on cellular adhesion and proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, we investigated the osteogenic potential of pre-osteoblasts on porous magnesia and yttria-stabilized zirconia ceramics (Hadjicharalambous et al, 2015b ), as well as the pre-osteoblastic cell response on zirconia, alumina, and zirconia/alumina composite (Hadjicharalambous et al, 2015a ). The objective of this study was to investigate the effect of zirconia and alumina ceramic substrate porosity on cellular adhesion and proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…Greater porosity of the material may be desirable for the growth of bone tissue, since the presence of interconnected pores allows cell migration and proliferation, as well as vascularization, effective fluid circulation, and transport of nutrients through the pores. However, excessively high porosity may compromise the mechanical properties of the scaffolds . Compared to porous scaffolds of alumina containing 5% nanometric zirconia inclusions, which showed the mechanical strength of 6.59 MPa, the alumina scaffold produced here showed lower mechanical resistance.…”
Section: Discussionmentioning
confidence: 83%
“…However, in porous form, this material is limited to application as bone grafts. Because it is bioinert, it is a strong candidate to replace metal in implants . Several studies have reported a greater efficacy of biodegradable synthetic substitutes, with non‐biodegradable alumina ceramics, supporting the use of this bioactive material in coatings .…”
Section: Introductionmentioning
confidence: 99%
“…3,4 The increased surface area of the porous structures leads to a better attachment to the host tissue. However, increased porosity compromises the mechanical properties of scaffolds, 28 as will be demonstrated below.…”
Section: Resultsmentioning
confidence: 99%